Electronic and transport properties of AlInN/AlN/GaN high electron mobility transistors. (August 2015) - Saidi, I.; Mejri, H.; Baira, M.; Maaref, H.
Highlights: Simulation of the band edges AlInN/AlN/GaN high electron mobility transistors. The confinement of subbands has accounted in calculating the electron mobility. The model adopted is improved by including the effects of deep electron traps. The AlInN/AlN/GaN HEMTs exhibit a self-heating. The drain voltage-dependent temperature in the conductive channel. Abstract: The present work is dedicated to simulate the band edges of AlInN/AlN/GaN high electron mobility transistors. In a second step, we have developed a model for the electron mobility by taking into account the predominant mechanisms. The confinement of subbands in the channel quantum well has also been accounted for in calculating the electron mobility. Obtained results have been used to calculate self-consistently the direct-current characteristics of AlInN/AlN/GaN HEMTs. As has been found, the drain current strongly depends on the electron band parameters. More especially, a drastic improvement in the electron transport is expected to be achieved by optimizing the deposited epilayers in terms of thicknesses and alloy composition. Based on an experimental support, the electronic model adopted is improved by including the effects of deep electron traps. As also shown, the AlInN/AlN/GaN HEMTs exhibit a self-heating. From the relevant direct current measurements, we have deduced the drain voltage-dependent temperature in the conductive channel.